Identification of single nucleotide polymorphisms in key glycogen metabolism genes of Crassostrea hongkongensis and their association with glycogen content - Lingxin Kong; Ziao Chen; Zhen Jia; Qiong Deng; Peng Zhu; Youhou Xu; Zhicai She (Frontiers in Marine Science)
Glycogen, a critical nutrient in Crassostrea hongkongensis, exhibits essential biological properties, with its quantitative levels serving as a pivotal parameter for phenotypic selection and genetic improvement of superior oyster strains. To investigate the characteristics of glycogen content and identify single nucleotide polymorphisms (SNPs) associated with this trait in C. hongkongensis, we cloned the full-length cDNA of key genes involved in glycogen metabolism, determined glycogen content and gene expression in different tissues and months of the oyster specimen collection, and developed SNPs in the gene coding region. The results demonstrated that glycogen synthase (ChGS) and glycogen phosphorylase (ChGP) are key genes regulating glycogen metabolism in C. hongkongensis. Both genes were ubiquitously expressed across all six analyzed tissues: gills, adductor muscle, mantle, labial palps, gonads, and digestive gland. Notably, mRNA expression levels of ChGS and ChGP in gonad and visceral tissues exhibited seasonal fluctuations, which showed significant correlation with glycogen content dynamics. Fifteen SNP markers were identified within the coding regions of ChGS and ChGP using fragment-length discrepant allele-specific polymerase chain reaction. The success rate of SNP identification was 37.5% (15/40). Using association analysis, one SNP located in the coding region of ChGS was found to be associated with glycogen content. These results provide potential molecular markers that can be used for the selection and breeding of glycogen traits in C. hongkongensis, and demonstrate the potential influence of ChGS and ChGP on glycogen content.